The Progress of Next Generation Sequencing in the Assessment of Myeloid Malignancies - Fulya Öz Puyan; Serhan Alkan (Balkan Medical Journal, 2019)

(untitled)
The introduction and advances on next-generation sequencing have led to novel ways to integrate simultaneous assessment of multiple target genes in routine laboratory analysis. Assessment of myeloid neoplasms with targeted next-generation sequencing panels shows evidence to improve diagnosis, assist therapeutic decisions, provide better information about prognosis, and better detection of minimal residual disease. Herein, we provide information for application and utilization of next-generation sequencing studies with a focus on the most important mutations in acute myeloid leukemia, myelodysplastic syndrome, myeloproliferative neoplasms, and other myelodysplastic/myeloproliferative neoplasms in order to integrate them into the daily clinical practice.